Platelet-Rich Plasma versus Corticosteroid Intra-Articular Injections for the Treatment of Trapeziometacarpal Arthritis: A Prospective Randomized Controlled Clinical Trial. - Malahias, Michael-Alexander; Roumeliotis, Leonidas; Nikolaou, Vasileios S; Chronopoulos, Efstathios; Sourlas, Ioannis; Babis, Georgios C (Cartilage, 2018)
Various systematic reviews have recently shown that intra-articular platelet-rich plasma (IA-PRP) can lead to symptomatic relief of knee osteoarthritis for up to 12 months. There exist limited data on its use in small joints, such as the trapeziometacarpal joint (TMJ) or carpometacarpal joint (CMCJ) of the thumb. A prospective, randomized, blind, controlled, clinical trial of 33 patients with clinical and radiographic osteoarthritis of the TMJ (grades: I-III according to the Eaton and Littler classification) was conducted. Group A patients (16 patients) received 2 ultrasound-guided IA-PRP injections, while group B patients (17 patients) received 2 ultrasound-guided intra-articular methylprednisolone and lidocaine injections at a 2-week interval. Patients were evaluated prior to and at 3 and 12 months after the second injection using the visual analogue scale (VAS) 100/100, shortened Disabilities of the Arm, Shoulder, and Hand Questionnaire (Q-DASH), and patient's subjective satisfaction. No significant differences between the baseline clinical and demographic characteristics of the 2 groups were identified. After 12 months' follow-up, the IA-PRP treatment has yielded significantly better results in comparison with the corticosteroids, in terms of VAS score ( P = 0.015), Q-DASH score ( P = 0.025), and patients' satisfaction ( P = 0.002). Corticosteroids offer short-term relief of symptoms, but IA-PRP might achieve a lasting effect of up to 12 months in the treatment of early to moderate symptomatic TMJ arthritis.